Ammonia level sensor using tapered optical fiber coated with titanium dioxide-incorporated porphyrin - Parasuti, Frazna; Hikmawati, Dyah; Trilaksana, Herri; Yasin, Moh. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
Since ammonia is water-soluble, environmental studies have shown that the industrial waste such as fertilizer manufacturing, food products, palm oil, urea fertilizer industry can cause very serious damage to water body ecosystems if not properly managed, resulting in a decrease in water quality. Devices based on optical technology, especially devices that combine optical fibers and nanomaterials, are identified as highly sensitive to the species of interest by detecting changes in physicochemical properties. A practical, easy-to-use, inexpensive instrument for detecting ammonia level was proposed using tapered optical fiber (TOF) coated with titanium dioxide-incorporated porphyrin. TOF was fabricated by simultaneously stretching and heating. The preparation of TiO2/porphyrin/gelatine was prepared to coat tapered optical fiber by dipping. SEM analysis shows an increase in length and a decrease in diameter, also the successful coating of titanium dioxide and porphyrin in the taper region. The EDX analysis also proves the presence of the Ti element in the TOF layer. The TOF produces significant sensing performances toward the ammonia liquid concentration level. The TOF coated with titanium dioxide-incorporated porphyrin can detect a one ppm difference in ammonia concentration with a certain range of output voltage for every concentration has.
Optica Applicata, Vol. 53, 2023, nr 3, s. 353-361
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; ammonia sensing; tapered optical fiber; titanium dioxide; porphyrin